Choice of Stent for Percutaneous Coronary Intervention of Saphenous Vein Grafts. (April 2017) - Iqbal, Javaid; Kwok, Chun Shing; Kontopantelis, Evangelos; de Belder, Mark A.; Ludman, Peter F.; Large, Adrian; Butler, Rob; Gamal, Amr; Kinnaird, Tim; Zaman, Azfar; Mamas, Mamas A.
Abstract : Background—: There are limited data on comparison of contemporary drug-eluting stent (DES) platforms, previous generation DES, and bare-metal stents (BMS) for percutaneous coronary intervention in saphenous vein grafts (SVG). We aimed to assess clinical outcomes following percutaneous coronary intervention to SVG in patients receiving bare-metal stents (BMS), first-generation DES, and newer generation DES in a large unselected national data set from the BCIS (British Cardiovascular Intervention Society). Methods and Results—: Patients undergoing percutaneous coronary intervention to SVG in the United Kingdom from January 2006 to December 2013 were divided into 3 groups according to stent use: BMS, first-generation DES, and newer generation DES group. Study outcomes included in-hospital major adverse cardiovascular events, 30-day mortality, and 1-year mortality. Patients (n=15 003) underwent percutaneous coronary intervention to SVG in England and Wales during the study period. Of these, 38% received BMS, 15% received first-generation DES, and 47% received second-generation DES. The rates of in-hospital major adverse cardiovascular events were significantly lower in patients treated with second-generation DES (odds ratio, 0.51; 95% confidence interval, 0.38–0.68; P <0.001), but not with first-generation DES, compared with BMS-treated patients. Similarly, 30-day mortality (odds ratio, 0.43; 95% confidence interval, 0.32–0.59; P <0.001) and 1-year mortality (odds ratio, 0.60; 95% confidence interval, 0.51–0.71; P <0.001) were lower in patients treated with second-generation DES, but not with first-generation DES, compared with the patients treated with BMS. Conclusions—: Patients receiving second-generation DES for the treatment SVG disease have lower rates of in-hospital major adverse cardiovascular events, 30-day mortality, and 1-year mortality, compared with those receiving BMS. Abstract : Supplemental Digital Content is available in the text.